Rhinovirus‐induced airway cytokines and respiratory morbidity in severely premature children (2015)
Background Rhinovirus (RV ) has been linked to the pathogenesis of asthma. Prematurity is a risk factor for severe RV infection in early life, but is unknown if RV elicits enhanced pro‐asthmatic airway cytokine responses in premature infants. This study investigated whether young children born severely premature (<32 wks gestation) exhibit airway secretion of Th2 and Th17 cytokines during natural RV infections and whether RV ‐induced Th2–Th17 responses are linked to more respiratory morbidity in premature children during the first 2 yrs of life. Methods We measured Th2 and Th17 nasal airway cytokines in a retrospective cohort of young children aged 0–2 yrs with PCR ‐confirmed RV infection or non‐detectable virus. Protein levels of IL ‐4, IL ‐13, TSLP , and IL ‐17 were determined with multiplex immunoassays. Demographic and clinical variables were obtained by electronic medical record (EMR ) review. Results The study comprised 214 children born full term (n = 108), preterm (n = 44) or severely premature (n = 62). Natural RV infection in severely premature children was associated with elevated airway secretion of Th2 (IL ‐4 and IL ‐13) and Th17 (IL ‐17) cytokines, particularly in subjects with history of bronchopulmonary dysplasia. Severely premature children with high RV ‐induced airway IL ‐4 had recurrent respiratory hospitalizations (median 3.65 hosp/yr; IQR 2.8–4.8) and were more likely to have at least one pediatric intensive care unit admission during the first 2 yrs of life (OR 8.72; 95% CI 1.3–58.7; p = 0.02). Conclusions Severely premature children have increased airway secretion of Th2 and Th17 cytokines during RV infections, which is associated with more respiratory morbidity in the first 2 yrs of life.